The relations between polycyclic aromatic hydrocarbons exposure and 1-OHP levels as a biomarker of the exposure - Klöslová, Zuzana; Drimal, Marek; Balog, Karol; Koppová, Kvetoslava; Dubajová, Jarmila (Central European Journal of Public Health, 2016)
BACKGROUND: Polycyclic aromatic hydrocarbons (PAHs) are the products of incomplete combustion or pyrolysis of various organic materials. Their ubiquity in the environment leads to measurable levels of exposure. However, the exposure varies strongly between different regions in Europe. Some PAHs with four or more rings are suspected to be human carcinogens. Therefore, the occupational and/or environmental exposure to PAHs may cause a significant health risk. The aim of investigation is to evaluate current levels of PAH exposure in defined groups of workers. METHODS: The industrial sites selected in this survey involved PAHs originating from coal tar pitch, carbon black, bitumen and rubber fumes. Based on the historical data, the sites were expected to exhibit quantifiable levels of exposure to PAHs. The total study population consisted of 139 persons: 108 (85 male and 23 female) workers were occupationally exposed in aluminum production, the production of graphite electrodes, road construction, or the rubber forming industry and 28 control individuals in two groups. RESULTS: The total 8 h time-weighted average (TWA) levels (sum of 16 components according to the EPA list) ranged from 0.2 to 773.7 μg.m(-3) (mean 26.7 μg.m(-3); 95th percentile 123.3 μg.m(-3)). The highest concentrations, as expected, were found in the aluminum production plant and production of graphite electrodes. The lowest concentrations were found in personal air samples of road construction workers. The concentrations of 1-hydroxypyrene as a pyrene metabolite in the urine of the exposed group of workers were found in levels between 0.11-1.26 μmol.mol(-1) creatinine before the exposure, and in the levels between 0.12-4.25 μmol.mol(-1) creatinine after the exposure 1-OHP concentrations in post-shift urine samples were highly correlated with the total airborne PAHs concentrations and pyrene concentrations in air. The correlation coefficients (r) between 1-OHP concentration and pyrene or total PAHs in air were 0.710 and 0.752 (p<0.05). CONCLUSION: This statistical analysis confirmed the effect of the occupational exposure to PAHs and pyrene on the body burden of workers. However, a modifying effect of sex, smoking habits, dietary intake, genetically modified metabolism, and the use of medication on the toxikokinetics of pyrene was not determined as significant.
Keywords: polycyklické aromatické uhlovodíky; Occupational Exposure; látky znečišťující vzduch v pracovním prostředí; Pyrenes; Humans; pyreny; průmysl; Environmental Monitoring; Female; Industry; lidé; Biomarkers; Polycyclic Aromatic Hydrocarbons; Slovakia; Slovenská republika; monitorování životního prostředí; biologické markery; ženské pohlaví; Male; pracovní expozice; Air Pollutants, Occupational; mužské pohlaví